The impact of board diversity on company performance: Panel data evidence from public listed companies in Malaysia - Ngeow, Shin Yee (2023)
In the current era, the case of graduate unemployment (GU) keeps on increasing due to the structural changes in the labour market and mismatch happens between employers' expectations on graduates’ capability in education and employability skills compared to graduates’ actual capability and expectation on a job. Throughout the whole research, the main objective of this study is to investigate the determinants of graduate unemployment in Malaysia through employability skills (ES), quality of education (QE), job expectations (JE) and market demand (MD). It is predicted that employability skills, quality of education, job expectations and market demand have a significant relationship with graduate unemployment. The research study is conducted using quantitative research designs in terms of descriptive research. It is decided to use a secondary data collection method to collect data information from the secondary platform such as Refinitiv, company’s annual report and etc. The sample comprise of 90 public listed companies in Malaysia from manufacturing industry, service industry as well as mining and quarrying industry from 2017 to 2022. Data collected is being examined through independent t-test, collinearity test and lastly the panel data regression analysis. The result shows that there is a significant positive relationship between gender diversity, age diversity and skill diversity with company ROE, on the other hand age diversity is positively significant to company Tobin’s Q performance. Also, it is found that gender diversity and age diversity show a significant difference before and during COVID-19 pandemic. With that, the companies, board of directors, policymakers, as well as regulators should be more aware on the values of accepting diversified gender, age and skill of the directors which will enhance company performance through strategic board decision making. It is also important to notice that organizations had to rapidly adapt to changing circumstances in terms of board diversity to stay competitive in the evolving market.